THE EFFECTS OF JOB STRESS, MOTIVATION AND WORK CONFLICT ON EMPLOYEE PERFORMANCE - Herminingsih, Anik (International Journal of Social Service and Research, 2025)
This study aims to analyze the effect of stress levels, work motivation, and work conflict on employee performance at PT Tira Austenite Tbk. The study's population comprised 340 employees, from which a sample of 185 was determined using the Slovin formula and random sampling method. Data analysis was performed using SEM Partial Least Square (SPLS) with the Smart-PLS version 3.0 program, involving two stages: the measurement model and the structural model. The measurement model was tested for validity through convergent validity, discriminant validity, and average variance extracted, while reliability was assessed using composite reliability and Cronbach's alpha. The results of the hypothesis test show that work stress does not have a significant effect on employee productivity, while work conflict has a negative and significant effect. The findings can inform management practices and interventions aimed at improving employee performance, ultimately contributing to more effective workforce management strategies. Furthermore, longitudinal studies that track changes in employee performance over time in response to implemented motivational strategies could provide valuable insights into the long-term effectiveness of such interventions.